2023
DOI: 10.3748/wjg.v29.i11.1685
|View full text |Cite|
|
Sign up to set email alerts
|

Factors affecting the quality of bowel preparation for colonoscopy in hard-to-prepare patients: Evidence from the literature

Abstract: Adequate bowel cleansing is critical for a high-quality colonoscopy because it affects diagnostic accuracy and adenoma detection. Nevertheless, almost a quarter of procedures are still carried out with suboptimal preparation, resulting in longer procedure times, higher risk of complications, and higher likelihood of missing lesions. Current guidelines recommend high-volume or low-volume polyethylene glycol (PEG)/non-PEG-based split-dose regimens. In patients who have had insufficient bowel cleansing, the colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 166 publications
1
5
0
Order By: Relevance
“…Our study revealed several critical findings, the first of which is the substantial difference in bowel preparation quality between constipated patients and controls. In accordance with previous studies [16,17], we observed that constipated patients, including younger patients with constipation, exhibited a lower rate of adequate bowel preparation (92.7% vs. 85.3%; p < 0.001) compared to controls. This suboptimal bowel preparation, a recognized challenge in the evaluation of constipation, not only impacts the quality of colonoscopy but also results in a decreased cecal intubation rate (96.1% vs. 85% and 84%; p < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed several critical findings, the first of which is the substantial difference in bowel preparation quality between constipated patients and controls. In accordance with previous studies [16,17], we observed that constipated patients, including younger patients with constipation, exhibited a lower rate of adequate bowel preparation (92.7% vs. 85.3%; p < 0.001) compared to controls. This suboptimal bowel preparation, a recognized challenge in the evaluation of constipation, not only impacts the quality of colonoscopy but also results in a decreased cecal intubation rate (96.1% vs. 85% and 84%; p < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“… 21 However, studies have reported that those undergoing colonoscopy were twice as likely to have inadequate bowel preparation compared to the general population, 22 , 23 a higher rate of procedural failure, 22 with lesions more likely to be missed. 24 The Raman blood test alone was thought to have an important role for these patients. Further research is needed to understand the utility and acceptability of Raman‐FIT or Raman alone specifically in these patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…FAC is an inflammatory pattern that may or may not be clinically relevant. It is most observed in adult patients with bowel preparation artifacts [9,10,[29][30][31][32][33], infectious colitis, drug-induced gastrointestinal injuries, and IBS. Less frequently, it may manifest as IBD [34,35], such as CD or partially treated UC.…”
Section: Discussionmentioning
confidence: 99%